2022
DOI: 10.3390/pharmaceutics14061238
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Surface Protein A-Hybrid Nanoparticles Protect Mice from Lethal Challenge after Mucosal Immunization Targeting the Lungs

Abstract: Pneumococcal disease remains a global burden, with current conjugated vaccines offering protection against the common serotype strains. However, there are over 100 serotype strains, and serotype replacement is now being observed, which reduces the effectiveness of the current vaccines. Pneumococcal surface protein A (PspA) has been investigated as a candidate for new serotype-independent pneumococcal vaccines, but requires adjuvants and/or delivery systems to improve protection. Polymeric nanoparticles (NPs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…A recent study showed that PspA immunization was more protective than the PCV13 against influenza-mediated secondary Spn infection but was not good against a high-dose (10 4 colony forming unit [CFU]) secondary Spn challenge 23 . To enhance the efficacy of protein vaccines and promote mucosal immune responses, there is emergent interest in the application of bacterial vesicles or other nanoparticles delivering candidate pneumococcal proteins as vaccines 24 26 . Recently, we have established a self-adjuvanting Yersinia pseudotuberculosis (Yptb) outer membrane vesicle (OMV) platform to deliver heterologous antigens to achieve protection against corresponding respiratory bacterial infections 27 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that PspA immunization was more protective than the PCV13 against influenza-mediated secondary Spn infection but was not good against a high-dose (10 4 colony forming unit [CFU]) secondary Spn challenge 23 . To enhance the efficacy of protein vaccines and promote mucosal immune responses, there is emergent interest in the application of bacterial vesicles or other nanoparticles delivering candidate pneumococcal proteins as vaccines 24 26 . Recently, we have established a self-adjuvanting Yersinia pseudotuberculosis (Yptb) outer membrane vesicle (OMV) platform to deliver heterologous antigens to achieve protection against corresponding respiratory bacterial infections 27 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Subcutaneous immunization with PspA has proven effective in protecting mice from fatal infections ( 63 ), while intranasal immunization with PspA has shown efficacy in protection against nasopharyngeal carriage in an adult mouse carriage model ( 64 , 65 ). Furthermore, mucosal vaccination with PspA has successfully elicited both mucosal and systemic immune responses ( 66 , 67 ). Initially, there were concerns that a vaccine targeting PspA might not provide adequate coverage due to its high variability ( 68 ).…”
Section: Protein Candidates For Pneumococcal Vaccinesmentioning
confidence: 99%
“…These results suggest the potential adjuvant activity of PLGA/chitosan NPs in stimulating systemic immune responses. The supposed mechanism of action is related to the maturation of DCs upregulating CD40, CD80, and CD86, triggered by the production of MHC II molecules [124]. Another report detailed an improved CD8 T-cell immune response after the prolonged release of M. tuberculosis antigen Mtb8.4 after a single administration.…”
Section: Plga Based Nano and Microparticles Dds For Vaccines Deliverymentioning
confidence: 99%